A Rare Syndrome and a Rare Association: Dandy–Walker Malformation and Cockayne Syndrome in a Child - Işıkay, Sedat; Bilgin, Burak; Karaer, Kadri; Şirikçi, Akif (Journal of Pediatric Neurology, 2019)
Cockayne syndrome is a rare autosomal recessive, neurodegenerative disorder characterized by a broad spectrum of clinical symptoms. Herein, we will describe a patient diagnosed with Cockayne syndrome by genetic testing who was also determined to be having Dandy–Walker malformation in brain imaging. In this article, we aimed to highlight the general characteristic findings of Cockayne syndrome and to report the togetherness of these two rare entities.
Keywords: Cockayne syndrome; Dandy–Walker malformation; child